2021
DOI: 10.1021/acsomega.1c03440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Conditions on Pd Speciation in CHA and Beta Zeolites for Passive NOx Adsorption

Abstract: The structure and evolution of Pd species in Pd-exchanged zeolite materials intended for use as passive NO x adsorbers were examined under various pretreatment conditions. Using in situ CO-diffuse reflectance infrared spectroscopy, Pd structures were characterized after 500 °C pretreatments in inert (Ar), water (1–2% H2O in Ar), oxidizing (air), and reducing (H2, CO) atmospheres. Two zeolites of similar Si/Al ratios but different framework topologies (Beta, CHA) were found to show different distributions of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Figure b shows a spectrum of CO adsorbed on Pd/H–CHA. The band at 2130 cm –1 is attributable to CO adsorbed on either Pd + or Pd 2+ . ,, The absence of this band after NO adsorption or after coadsorption of CO and NO is consistent with the stronger adsorption of NO than CO (see more on this topic below) and the displacement of adsorbed CO by NO illustrated in Figure b. This result matches the aforementioned TPD experiments that demonstrate that there is no formation of a NO/CO coadsorbed complex.…”
Section: Resultssupporting
confidence: 81%
“…Figure b shows a spectrum of CO adsorbed on Pd/H–CHA. The band at 2130 cm –1 is attributable to CO adsorbed on either Pd + or Pd 2+ . ,, The absence of this band after NO adsorption or after coadsorption of CO and NO is consistent with the stronger adsorption of NO than CO (see more on this topic below) and the displacement of adsorbed CO by NO illustrated in Figure b. This result matches the aforementioned TPD experiments that demonstrate that there is no formation of a NO/CO coadsorbed complex.…”
Section: Resultssupporting
confidence: 81%
“…Such treatment results in an almost atomic dispersion of palladium in the zeolite pores. 23,30,33,34 Depending on pretreatment conditions, palladium is observed in oxidation states of Pd 0 , Pd I , and Pd II , and even Pd IV has been suggested. Many studies revealed the presence of Pd 2+ cations and [Pd II PdO, and PdO 2 have been proposed to contribute to the NO x storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites investigated thus far in PNA research have MFI, BEA, ,, CHA, ,, or FER framework topology. The investigations revealed that the storage mechanism of NO x on these Pd-loaded zeolites is complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 Recently, passive NO x adsorbers (PNAs) have been considered an attractive technology for removing NO x from the cold-start exhaust of diesel vehicles, directly adsorbing NO x gases at low temperatures and releasing them at a temperature where SCR systems can operate efficiently. 7 Noble metals supported on both zeolites and oxides have been studied as PNA materials. 5,7 Among those, Pd-based zeolites (such as Pd/Beta, Pd/SSZ-13 and Pd/ZSM-5) are of particular interest because of their excellent resistance to hydrothermal aging.…”
Section: Introductionmentioning
confidence: 99%